1970
DOI: 10.1021/ja00712a052
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecificity of the enzymic synthesis of the o-xylene ring of riboflavin

Abstract: Cryptates, a new type of metal cation complexes, have been described recently.12 It was found that the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
0

Year Published

1970
1970
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 1 publication
2
52
0
Order By: Relevance
“…1) that had been proposed earlier. A nucleophilic attack of one molecule of 6,7-dimethyl-8-ribityllumazine (exomethylene form, 1a) at C-6 of a second molecule of 6,7-dimethyl-8-ribityllumazine covalently bound at the acceptor site of the protein (2) could yield intermediate 3 (4,10,11). Deprotonation of 3 at C-7a and protonation at N-1 could afford 7.…”
Section: Isolation Of a Transient Molecular Species (Compound Q)mentioning
confidence: 99%
See 2 more Smart Citations
“…1) that had been proposed earlier. A nucleophilic attack of one molecule of 6,7-dimethyl-8-ribityllumazine (exomethylene form, 1a) at C-6 of a second molecule of 6,7-dimethyl-8-ribityllumazine covalently bound at the acceptor site of the protein (2) could yield intermediate 3 (4,10,11). Deprotonation of 3 at C-7a and protonation at N-1 could afford 7.…”
Section: Isolation Of a Transient Molecular Species (Compound Q)mentioning
confidence: 99%
“…The enzyme-catalyzed reaction requires the simultaneous presence of two substrate molecules with an essentially antiparallel orientation at the active site of the enzyme (4). Ligandbinding studies confirmed that each subunit of the homotrimeric riboflavin synthase can bind two lumazine molecules (7).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…1); more specifically, that reaction involves the transfer of a four-carbon moiety between two DMRL molecules serving as donor and acceptor, respectively (10 -13). Both reactions are thermodynamically irreversible (9, 14) and can proceed in the absence of a catalyst (11,(15)(16)(17).LS from fungi are c 5 -symmetric homopentamers, whereas the enzymes from plants, Archaea, and most eubacteria studied are 532 symmetric capsids of 60 identical subunits, which are best described as dodecamers of pentamers. The subunit folding patterns of pentameric and icosahedral LS are similar.…”
mentioning
confidence: 99%
“…Later, Rowan and Wood (13) and Plaut and Beach (14) extended these observations and showed that the uncatalyzed reaction can proceed in neutral as well as in acidic aqueous solution. The uncatalyzed and the enzymecatalyzed reactions were shown to proceed with the same regiospecificity (5,19).…”
Section: Resultsmentioning
confidence: 99%